GENETIC VARIANTS AND SERUM PROFILES OF CYTOKINES IN COVID-19 SEVERITY. Issue 1 (16th January 2023) - Alefishat, Eman; Mousa, Mira; Albreiki, Mohammed; Jelinek, Herbert F.; Al Halwachi, Zainab; Khalili, Mariam; Waasia, Fathimathuz; Uddin, Maimunah; Al Kaabi, Nawal; Mahboub, Bassam; Albataineh, Mohammad T.; Tay, Guan K.; et al.
ABSTRACT: Background: Patients with severe coronavirus disease 2019 (COVID-19) are at an increased risk of acute respiratory distress syndrome and mortality. This is due to the increased levels of pro-inflammatory cytokines that amplify downstream pathways that are controlled by immune regulators. Objective: This study aimed to investigate the association between cytokine genetic variants, cytokine serum levels/profiles, and disease severity in critically and noncritically ill COVID-19 patients. Methods: This cross-sectional study recruited 646 participants who tested positive for severe acute respiratory syndrome coronavirus 2 from six collection sites across the United Arab Emirates. Medical files were accessed to retrieve clinical data. Blood samples were collected from all participants. Patients were divided into two clinical groups, noncritical (n = 453) and critical (n = 193), according to World Health Organization classification guidelines for COVID-19 patients. Cytokine analyses were conducted on serum of a subset of the cohort, specifically on 426 participants (noncritical, 264; critical, 162). Candidate gene analyses of 33 cytokine-related genes (2, 836 variants) were extracted from a genome-wide association study to identify genetic variants with pleiotropic effects on a specific cytokine and the severity of COVID-19 disease. Results: Age, body mass index (BMI), and pre-existing medical conditions were found to be significant risk factors that contribute to COVID-19 disease severity. After correcting for age, sex, and BMI, IP-10 ( P < 0.001), IFN ( P = 0.001), IL-6 ( P < 0.001), and CXCL-16 ( P < 0.001) serum levels were significantly higher among critical COVID-19 cases, when compared with noncritically ill patients. To investigate if the genetic variants involved in the serum cytokine levels are associated with COVID-19 severity, we studied several genes. Single nucleotide polymorphisms in IL6 (rs1554606; odd ratio (OR)G = 0.67 [0.66, 0.68]; P = 0.017), IFNG (rs2069718; ORG = 0.63 [0.62, 0.64]; P = 0.001), MIP (rs799187; ORA = 1.69 [1.66, 1.72]; P = 0.034), and CXCL16 (rs8071286; ORA = 1.42 [1.41, 1.44]; P = 0.018) were found to be associated with critically ill patients. Polymorphisms in the CXCL10, CCL2, IL1, CCL7, and TNF genes were not associated with the COVID-19 critical phenotype. The genotypes of IL-6 (gene, IL6 [7p15.3]) and CXCL-16 (gene, CXCL16 [17p13.2]) were significantly associated with the serum levels of the respective cytokine in critical cases of COVID-19. Conclusion: Data obtained from measuring cytokine levels and genetic variant analyses suggest that IL-6 and CXCL-16 could potentially be used as potential biomarkers for monitoring disease progression of COVID-19 patients. The findings in this study suggest that specific cytokine gene variants correlate with serum levels of the specific cytokine. These genetic variants could be of assistance in the early identification of high-risk patients on admission to the clinic to improve the management of COVID-19 patients and other infectious diseases.